Inductive and deductive grammar teaching - Felipe Soriano, Rosa Milagros (2022)
The objective of this research work is as we already know, the teaching of grammar has been a quite complex topic for the teacher who teaches this subject, which is often not completely relevant when teaching the English language but at the same time very important in learning a foreign language.In fact, the language has had and has variations in teaching methods and approaches when it you eat grammar. As we know, there are some difficulties in teaching the language effectively, especially to people who have English as a second language. Grammar is an important component of any language as it involves the use of rules to achieve language understanding goals and the language itself. For this reason, it is important to know the teaching process of teachers regarding the grammar that learning a new language details.